Study The Effect Of Thermal Treatment On The Mechanical Properties Of Bioplastic Produced By 3d Printer - Raghs, Hamdi Abdulhamid (Journal of Pure & Applied Sciences, 2022)
In this study, it was investigated whether the load strength of bio plastic (PLA) specimens produced in a three-dimensional printer can be increased by applying the temperature and dwell time variables were applied, by performing 9 different experiments. ASTM D638 standard procedure is adopted for evaluating the tensile behaviour of 3D-printed PLA test specimens. It was examined whether there was a change in the material structure and interpretation was made according to the results. Experimental studies primarily started with the production of samples with a 3D printer. In the first three samples, the temperature was kept constant at 100 ℃, then the fourth, fifth and sixth samples were kept under 150°C, The last three samples were kept at 200°C, and the waiting times were adjusted to 25, 50, and 75 minutes, respectively, for samples. Test samples 7, 8 and 9 could not withstand the high temperature, so the tensile test could be performed up to the number 6 sample. In order to investigate the changes in the heat treated samples, the tensile test was applied to the untreated sample and the remaining 6 samples. After testing the samples, yield strength, tensile strength, maximum tensile and modulus of elasticity values were compared. As a result of the test, positive results were observed in yield strength when the untreated sample was compared with the heat treated samples, which shows that the heat treatment has a positive effect on the samples, and also the effect of heat treatment led to an increase elasticity modulus, As per the effect on the bio plastic surface according to the graphs, the specimen roughness was found to vary depending on the temperature because temperature affects in surface roughness. In our attempts, investigations will have performed by Optical microscope analysis, Surface Roughness Measurement, and tensile testing and this will help us to explain properties of the samples and changes likely to occur in the course of the experiments. The aim of this research is improve the mechanical properties of bio plastic by thermal treatment.